2021
DOI: 10.1101/2021.10.15.464611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-TRAP/SSP2 monoclonal antibodies can inhibit sporozoite infection and enhance protection of anti-CSP monoclonal antibodies

Abstract: Vaccine-induced sterilizing protection from infection with the Plasmodium parasite, the pathogen that causes malaria, will be an essential tool in the fight against malaria as it would prevent both malaria-related disease and transmission. Stopping the relatively small number of parasites injected by the mosquito before they can migrate from the skin to the liver is an attractive goal. Antibody-eliciting vaccines have been used to pursue this objective by targeting the major parasite surface protein present du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…A recent manuscript in preprint has shed some light on this and has demonstrated that anti-TRAP mAbs can significantly improve the protective efficacy of anti-CSP mAbs in both rodent models and liver-humanized mice to above 80% at low doses. 68 However, whether this enhancement is additive or synergistic was not addressed and will be critical for determining the utility of such combinations. Together, these data suggest that combinations of PE mAbs may be a pathway to achieving high levels of protection at serum concentrations achievable over extended periods.…”
Section: "Pre-erythrocytic" Stage Targeted Monoclonal Antibodiesmentioning
confidence: 99%
“…A recent manuscript in preprint has shed some light on this and has demonstrated that anti-TRAP mAbs can significantly improve the protective efficacy of anti-CSP mAbs in both rodent models and liver-humanized mice to above 80% at low doses. 68 However, whether this enhancement is additive or synergistic was not addressed and will be critical for determining the utility of such combinations. Together, these data suggest that combinations of PE mAbs may be a pathway to achieving high levels of protection at serum concentrations achievable over extended periods.…”
Section: "Pre-erythrocytic" Stage Targeted Monoclonal Antibodiesmentioning
confidence: 99%